2000
DOI: 10.1590/s0004-282x2000000200002
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction in epilepsy: identifying the psychological variables

Abstract: -In order to evaluate the psychological variables that affect sexual dysfunction (SD) in epilepsy, where compared 60 epileptics (Group 1) with 60 healthy individuals (Group 2), through the State-Trait Anxiety Inventory (Spielberger et al., 1970), Beck Depression Inventory (Beck, 1974) and Sexual Behavior Interview (Souza, 1995). Sexual dysfunction (SD), anxiety and depression were found more frequently in Group 1 than in Group 2 and were not related to sex. Variables such as the onset duration and frequency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 19 publications
0
24
0
3
Order By: Relevance
“…However, all patients in this study were submitted to psychological and urological evaluations. Previously, Souza et al 35 reported a significant association between sexual dysfunction, anxiety, and depression in male and female patients with epilepsy. Depressive disorders, which are frequently observed in patients with epilepsy 36 , may cause sexual dysfunction.…”
Section: Discussionmentioning
confidence: 97%
“…However, all patients in this study were submitted to psychological and urological evaluations. Previously, Souza et al 35 reported a significant association between sexual dysfunction, anxiety, and depression in male and female patients with epilepsy. Depressive disorders, which are frequently observed in patients with epilepsy 36 , may cause sexual dysfunction.…”
Section: Discussionmentioning
confidence: 97%
“…Epilepsy signifies anxiety and depression, low self-esteem and immaturity as a result of the seizure, and this could lead to avoid situations that call for affective sexual involvement. 17,30,31 The prevalence of depression was found to increase among patients having epilepsy with secondary generalization, mainly when correlated with duration of disease, intractability, and polymedication. 17 The high prevalence of performance anxiety (65.9%) among our patients could be attributed to response to the fear of failure and this may result in psychogenic ED.…”
Section: Discussionmentioning
confidence: 99%
“…7,12,14 The resultant neuroendocrine effects with steroid sex hormone alterations may alter epileptogenicity. [15][16][17] Organic etiologies such as vasculogenic erectile dysfunction (ED) were infrequently reported in men with epilepsy. 18 In addition, psychosocial variable can contributed to a great extent as a cause of altered sexual responsiveness in patients with epilepsy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of depression is increased among patients with epilepsy, mainly when correlated with duration of disease, intractability, and polymedication. 94 Epilepsy signifies anxiety and depression, low selfesteem and immaturity and this could lead to avoid situations that call for affective sexual involvement. 95…”
Section: Hamedmentioning
confidence: 99%